Root traits and their potential links to plant ideotypes to improve drought resistance in common bean - Polanía Perdomo, José A.; Poschenrieder, Charlotte; Rao, Idupulapati M.; Beebe, Stephen E. (Springer, 2017)
Drought stress limits growth and yield of crops, particularly under smallholder production systems with minimal use of inputs and edaphic limitations such as nitrogen (N) deficiency. The development of genotypes adapted to these conditions through genetic improvement is an important strategy to address this limitation. The identification of morpho-physiological traits associated with drought resistance contributes to increasing the efficiency of breeding programs. A set of 36 bean genotypes belonging to the Middle American gene pool was evaluated. A greenhouse study using soil cylinders was conducted to determine root vigor traits (total root length and fine root production) under drought stress. Two field trials were conducted to determinate grain yield, symbiotic nitrogen fixation (SNF) ability and other shoot traits under drought stress. Field data on grain yield and other shoot traits measured under drought were related with the greenhouse data on root traits under drought conditions to test the relationships between shoot traits and root traits. Response of root vigor to drought stress appeared to be related with ideotypes of water use (water savers and water spenders). The water spender ideotypes presented deeper root system, while the water saver ideotypes showed a relatively shallower root system. Increase in SNF ability under drought stress was associated with greater values of mean root diameter while greater acquisition of N from soil was associated with finer root system. We identified seven common bean lines (SEA 15, NCB 280, SCR 16, SMC 141, BFS 29, BFS 67 and SER 119) that showed greater root vigor under drought stress in the greenhouse and higher values of grain yield under drought stress in the field. These lines could serve as parents for improving drought resistance in common bean.